Exploring the role of china’s civilized cities in attracting foreign direct investment. A way forward to sustainable socioeconomic development - Han, Jiabin; Chen, Ziyi; Rehman, Alam; Zeeshan, Muhammad (Frontiers in Environmental Science, 2022)
The cities dynamics and structures can be vital to attract foreign direct investment. Therefore, foreign investors prefer cities where they are confronted to lower volume or none of unexpected happening. The civilized locality is likely to be supportive in the operations of any business activity rendered by local or foreign firms. As the “highest honor” in the selection of cities, civilized cities have an important impact on attracting foreign direct investment. The paper attempts to evaluate the civilized cities as a quasi-natural experiment, and uses the staggered difference-in-difference model to evaluate the effect and mechanism of civilized cities evaluation on the FDI of selected cities. The results show that the honorary title of civilized city has a reputation of cumulative effect, and can significantly increase the scale of foreign direct investment in the city independent of the brands of low-carbon city, smart city, innovative city and pilot free trade zones. The three main ways to attract foreign investments can be materialized through enhancing urban infrastructure, attracting labor inflow and improving science and technology innovation.